Travel Satisfaction of Persons with Disabilities in Metropolitan Indonesia: A Case of Jakarta - Fitri, Husnul; Lesmawati, Diah Rini (The Center for Disability Studies and Services Brawijaya University, 2024)
Many studies have been conducted on travel satisfaction with public transportation in various countries. However, no studies have reached inclusive groups such as persons with disabilities, although most of them depend on public transportation. Knowledge about travel satisfaction of persons with disabilities can be a reference for improving public transportation services that are adequate to the mobility needs of persons with disabilities. Therefore, this study aims to determine the travel satisfaction of persons with disabilities regarding public transportation in Jakarta using the Satisfaction to Travel (STS) measurement scale. The results of this study show not only the satisfaction of persons with disabilities with public transportation but also the influence of duration factors and the number of variations in transportation modes used.